Complete genome sequence of Oscillibacter valericigenes Sjm18–20T (=NBRC 101213T). Issue 3 (May 2012) - Katano, Yoko; Fujinami, Shun; Kawakoshi, Akatsuki; Nakazawa, Hidekazu; Oji, Syoko; Iino, Takao; Oguchi, Akio; Ankai, Akiho; Fukui, Shigehiro; Terui, Yasuyuki; Kamata, Sachi; Harada, Takeshi; et al.
Abstract Oscillibacter valericigenes is a mesophilic, strictly anaerobic bacterium belonging to the clostridial cluster IV. Strain Sjm18–20T (=NBRC 101213T =DSM 18026T ) is the type strain of the species and represents the genusOscillibacter Iinoet al. 2007. It was isolated from the alimentary canal of a Japanese corbicula clam (Corbicula japonica ) collected on a seacoast in Shimane Prefecture in Japan. Phylogenetically, strain Sjm18–20T is closest to uncultured bacteria in digestive tracts, including the enriched cells thought to representOscillospira guilliermondii Chatton and Perard 1913. The isolated phylogenetic position and some distinct characteristics prompted us to determine the complete genome sequence. The 4, 410, 036 bp chromosome and the 60, 586 bp plasmid were predicted to encode a total of 4, 723 protein-coding genes.